PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP KEMISKINAN DI PROVINSI JAWA BARAT - Dwi Ardian; Muhammad Rizqi Destanto (Seminar Nasional Official Statistics, 2020)
Poverty is still a major problem in developing countries like Indonesia. One province that has contributed to the poverty of Indonesia is the Province of West Java. West Java is the third poorest population in indonesia, contributing to 13.79 percent, just under East Java and Central Java. Poverty is a complex problem that needs more attention to its treatment. It takes an in-depth study to determine what variables of socio-economic factor must take priority in dealing with poverty. This study tries to identify and examine the factors affecting poverty in the Province of West Java. The data used is by the 2014-2018 panel data released by the Central Statistics Office of Indonesia (BPS) provincesties/cities of West Java and other available data from Ministry of Finance Indonesia (Kemenkeu). The method used in this study is panel data regressions into the presumed variables are affecting poverty based on expert theories. The results have been economic growth, the open unemployment rate (TPT), the public allocation fund (DAU), and the population density has no significant impact on poverty in West Java. The human development index variable (ipm), compiled for school average, school-time hopes, life expectancy, and per capita spending, has a significant impact on poverty. So the step that government must take are to ensure public health with adequate facilities, providing educational facilities including teachers who not only have enough from the quantity side but also have high quality. Another attempt is to ensure stability at prices and maintain purchasing power of society with adequate income and or affordable price of needs.